A higher composite dietary antioxidant index is associated with a decreased risk of subclinical hyperthyroidism in adults: evidence from epidemiological studies - Wu, Jie; Niu, Junxian; Jia, Chuyu; Yang, Qingkai; Li, Dewei; Dong, Xuqin (Frontiers in Nutrition, 2025)
Background and objectiveThyroid dysfunction is closely related to oxidative stress, and the intake of dietary antioxidants may affect thyroid function by regulating oxidative stress. The composite dietary antioxidant index (CDAI) is used as an indicator to measure the overall antioxidant capacity of the diet by quantifying the intake of these various antioxidants. However, its association with thyroid dysfunction has not been clearly established. This study aimed to investigate the association between CDAI and thyroid dysfunction in a nationally representative sample of U.S. adults.MethodsFor this research, data was drawn from the National Health and Nutrition Examination Survey (NHANES) conducted in the United States between 2007 and 2012. The study population comprised 5,956 adults age ≥ 20 years. It investigated the association between CDAI and subclinical hyperthyroidism (SCHyper) as well as other thyroid dysfunctions through multivariate logistic regression and restricted cubic spline analysis (RCS).ResultsAfter adjusting for covariates, our research revealed that an increase in CDAI is significantly associated with a reduced risk of SCHyper [OR = 0.90, 95% CI = (0.82, 0.99), p = 0.03]. The risk of SCHyper in the highest CDAI quartile (Q4) was reduced by 57.0% compared to the lowest group (Q1) [OR = 0.43, 95% CI = (0.20, 0.92)]. Non-linear analysis indicated an L-shaped curve relationship between CDAI and SCHyper. Subgroup analysis and interaction terms suggested that race and poverty to income ratio (PIR) subgroups affect the relationship between CDAI and incidence of SCHyper. And, the protective effect of CDAI against SCHyper was more particularly stronger in non-Hispanic whites and high-income (PIR > 3.5) populations.ConclusionHigher CDAI scores were independently associated with a reduced risk of SCHyper, suggesting that dietary antioxidants may protect thyroid function by alleviating oxidative stress. These results offer new insights into the prevention and treatment of patients with SCHyper.